5+3(s-5t)=

Simple and best practice solution for 5+3(s-5t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3(s-5t)= equation:


Simplifying
5 + 3(s + -5t) = 0
5 + (s * 3 + -5t * 3) = 0
5 + (3s + -15t) = 0

Solving
5 + 3s + -15t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + 3s + -5 + -15t = 0 + -5

Reorder the terms:
5 + -5 + 3s + -15t = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 3s + -15t = 0 + -5
3s + -15t = 0 + -5

Combine like terms: 0 + -5 = -5
3s + -15t = -5

Add '15t' to each side of the equation.
3s + -15t + 15t = -5 + 15t

Combine like terms: -15t + 15t = 0
3s + 0 = -5 + 15t
3s = -5 + 15t

Divide each side by '3'.
s = -1.666666667 + 5t

Simplifying
s = -1.666666667 + 5t

See similar equations:

| 19b-9b=35 | | 14v-9b=35 | | 1000+x(10)=2000 | | 3y-2x=3 | | 8.9*10= | | -6x+24=24-9x | | 3(x+2)=32 | | (t-3)2-(t-2)2=5 | | (2x-1)*x=91 | | 70+2m=24m^2 | | 2+a=3(6a-5) | | (2x^2)-4x-30=0 | | (2x-1)x=91 | | r^2+9=6r | | 305+x(5)=350 | | 5x=-37 | | 10=-2x+8 | | 1x+15=25+12x | | -50=19+x | | x+6=-5x+5x | | -7+5=12 | | 6x+42-13x=24 | | x^2+16x+64=-9 | | 7(3x+9)-6(2x+5)= | | 6240000/100= | | 2800+x(150.99)=5819.80 | | -8(2x-4)+7(3+5x)= | | b+3=b*3 | | 6r-6r=-5+r | | A(A-12)-15=30 | | 2y-5+7=-32 | | 2x+10-x+55=90 |

Equations solver categories